Pengaruh Naungan terhadap Beberapa Karakter Morfologi dan Fisiologi pada Varietas Kedelai Ceneng - Ahmad Sutopo (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
Soybeans will respond differently to shade conditions. One of the obstacles on sheltered land is the lack of sunlight intensity and light energy that can be received by plants. Adaptation to shade conditions can be achieved if plants have the mechanism of capture and use of light efficiently. The purpose of this experiment was to determine the effect of shade on morphological characters, and physiology on Ceneng soybean varieties. The experimental design used was Split Plot Design with the main plot was the level of shade and subplot are soybean varieties . The results showed that the shade treatment affected the growth and yield of soybean by decreasing the percentage of growth in germination, root dry weight, number of root nodules, anthocyanin pigment content, leaf total sugar content, slower flower emergence time, number of flowers at harvest, amount total pods and pod weight, but on the contrary there was no increase in shade-free soybean plants. While the shade treatment also influenced the increase in growth and yield of soybean plants by increasing plant height, number of leaves, number of branches, length, width, leaf area index, chlorophyll a pigment, chlorophyll b and rubberenoid, canopy wet weight, canopy dry weight, moisture content canopy, root water content, decreased number of empty pods and number of filled pods, but vice versa did not occur in shade-free soybean plants.